Resposta hemodinâmica fetal ao exercício isométrico materno - Paz, Monique Soares (2019)
Objectives: To assess the fetal response by use of Doppler study in diabetes pregnant women submitted to isometric exercise. Methods: A cross-sectional experimental study was conducted on 25 diabetes pregnant women with gestational age between 26 and 36 weeks. The patients were submitted to isometric handgrip, and data were collected from the mother (blood pressure, heart rate and Doppler velocimetry for the uterine arteries) and from the fetus (heart rate, Doppler velocimetry for the umbilical artery, middle cerebral artery and ductus venosus). All variables were collected before, during and after the isometric handgrip. Results: There was a significant reduction in the pulsatility index (average values pre 0,77±0,30, trans 0,65±0,22, and post 0,75±0,22, with p=0,001), resistance index (average values pre 0,49±0,12, trans 0,44±0,10, and post 0,48±0,90, with p=0,000) and Systole/Diastole ratio (average values pre 2,09±0,59, trans 1,87±0,40, and post 2,71±3,43, with p<0,002) of the right uterine artery. These variables were only altered significantly during isometric and not when compared to the pre and post-isometric values. There was also a significant reduction in the pulsatility index (average values pre 0,80±0,38, trans 0,69±0,17, and post 0,75±0,25, with p=0,027), resistance index (average values pre 0,50±0,12, trans 0,46±0,07, and post 0,50±0,10, with p=0,039) and Systole/Diastole ratio (average values pre 2,23±1,12, trans 1,93±0,30, and post 2,07±0,49, with p<0,023) of the left uterine artery. These variables were not altered when compared to pre and post-isometric values, as were they not altered during and post-isometric. There was no significant difference in the foetal parameters when compared before, during or after the isometric test. Conclusion: We conclude there was significant reduction in the pulsatility index , resistance index and Systole/Diastole ratio of the right uterine artery only during isometric and not when compared to pre and post-isometric values. There was also significant reduction in the pulsatility index, resistance index and Systole/Diastole ratio of the left uterine artery. These variables were not altered when compared to pre and post-isometric values, as were they not altered during and post-isometric. The vasodilatation mechanism of the uterine arteries demonstrates the compensation and hemodynamic homeostasis of the gestational period, confirmed by the foetal parameters that don’t present alterations when compared before, during or after the isometric test.